Sadar Hukum Online Speech di Media Sosial untuk Anggota Karang Taruna Desa Tunggilis - rakhman, Yadi; Nursyanti, Reni; Ruddiya Ilmalyaqin, Muhammad Azhar (Pusat Studi Teknologi Informasi Fakultas Ilmu Komputer Universitas Bandar Lampung, 2025)
The expansion of internet access facilitates learning, work, social interaction, and transactions; however, it also increases the risks of hoaxes and cyberbullying, which carry legal and psychosocial consequences. High levels of misinformation and low digital-ethics literacy—as reflected in the national cybersecurity index—underscore the need for systematic, structured educational interventions. The community engagement program “Legal Awareness of Online Speech on Social Media” is aimed at members of the Tunggilis Village Karang Taruna (Kalipucang Subdistrict, Pangandaran Regency) to strengthen their understanding of internet ethics, the legal consequences of online interactions, and safe social-media practices. The methods include a pre-test, lecturer-led counseling sessions, hands-on mentoring, and a Google Form–based post-test; the activities are scheduled for 21–23 July 2025 at the Tunggilis Village Office Hall. The output targets are: at least 90% of participants understand the principles of healthy internet practices, and at least 85% understand the legal aspects of online interactions. The program is expected to foster ethical and resilient digital behavior among village youth while providing a replicable good practice.